PENGARUH PUPUK ORGANIK CAIR (POC) URINE SAPI FERMENTASI TERHADAP TANAMAN JAGUNG HYBRID (The Effects of organic fertilizer (POC) Fermented Cow Urine in Hybrid Corn) - Nuryanto, Nuryanto; Sumaryanto, Sumaryanto (UPPM Politekik Pembangunan Pertanian Yogyakarta Magelang (Polbangtan Yoma), 2018)
This study done from September to December 2017 in Desa Pagersari , Mungkid, Magelang. Land area of 1,000 m2 divided by 36 plots, planted by hybrid corn (70 cmx15cm) which is two seeds per hole. When 10th day after plant it fertilized by 10 kg of NPK, 7kg of Urea, 4 kg of SP-36. When 28th day after plant it randomly divide into 6 kinds of dosage treatment of POC fermented cow urine in 0 ml, 100 ml, 200 ml, 300 ml, 400 ml and 500 ml each tree and it repeated by 6 times. The variables refers by height of plant, Bagan Warna Daun (BWD), diameter of stem, harvest weight without klobot, dry weight of corn seed and weight each 100 seed. Measurement results at 60th day after plant, reach 284 cm height, 1.89 cm stem diameter and the BWD entered the category four. The result show that hybrid corn that not fertilized by POC fermented cow urine (control) have harvest weight without klobot was 157 gr/cob that significantly different (P<0.01) increased by 15.28% to 181 gr/cob, dry weight of corn seed was 124 gr/cob that significantly different (P <0.01) increased by 11.29% to 138 gr/cob and the weight each 100 seed was 24.33 gr that significantly different (P <0.01) increased by 6.34% to 28gr/100 seed on hybrid corn that fertilized by POC fermented cow urine 100 ml/stem. In the fertilization more than 100 ml/stem, there is likely to be an unstable increase (P> 0.05) to the harvest weight without klobot, dry weight corn seed and weight each 100seeds. Based on this, for the efficiency and production of hybrid corn, the dose of fertilization of both aged 28 th after plant with POC fermented cow urine is 100 ml/stem.Keywords: POC, hybrid corn